2013
DOI: 10.1161/cir.0b013e31829b2be6
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular Function and Treatment in β-Thalassemia Major

Abstract: This aim of this statement is to report an expert consensus on the diagnosis and treatment of cardiac dysfunction in β-thalassemia major (TM). This consensus statement does not cover other hemoglobinopathies, including thalassemia intermedia and sickle cell anemia, in which a different spectrum of cardiovascular complications is typical. There are considerable uncertainties in this field, with a few randomized controlled trials relating to treatment of chronic myocardial siderosis but none relating to treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
190
0
9

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 331 publications
(199 citation statements)
references
References 315 publications
(412 reference statements)
0
190
0
9
Order By: Relevance
“…Importantly, 72.7% of patients treated with deferasirox and 54.5% of patients treated with DFO improved from severe (T2* <10 ms) to mild-to-moderate (T2* 10-20 ms) myocardial iron overload after 24 months-a clinically important increase since the relative risk of heart failure in patients with myocardial T2* <10 ms compared with T2* >10 ms has been shown to be significantly higher (relative risk 160 [95% CI 39-653]) [20]. This study did not evaluate chelation in patients with the most severe levels of myocardial iron overload (T2* <6 ms), where therapy based on a combination of DFO and deferiprone is advised [17].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Importantly, 72.7% of patients treated with deferasirox and 54.5% of patients treated with DFO improved from severe (T2* <10 ms) to mild-to-moderate (T2* 10-20 ms) myocardial iron overload after 24 months-a clinically important increase since the relative risk of heart failure in patients with myocardial T2* <10 ms compared with T2* >10 ms has been shown to be significantly higher (relative risk 160 [95% CI 39-653]) [20]. This study did not evaluate chelation in patients with the most severe levels of myocardial iron overload (T2* <6 ms), where therapy based on a combination of DFO and deferiprone is advised [17].…”
Section: Discussionmentioning
confidence: 92%
“…The 1-year extension to the CORDELIA study generated long-term data on the efficacy and safety of deferasirox or DFO in patients with myocardial siderosis when treated for up to 2 years, adding to the body of evidence supporting a consensus statement on the use of these chelators in the treatment of myocardial siderosis in patients without cardiac decompensation [17]. Deferiprone monotherapy is also recommended in patients with myocardial siderosis; however, prospective data beyond 1 year of treatment are limited.…”
Section: Discussionmentioning
confidence: 99%
“…We had previously shown that CMR could be performed quickly in Thailand13 for a single indication, evaluation of cardiac iron, in a cohort where the clinical value for mortality and morbidity of this measurement is established 25. However, in this first pilot project, an approach was taken focusing on technology delivery with less investment in education and mentoring.…”
Section: Discussionmentioning
confidence: 99%
“…The 2013 American Heart Association (AHA) guidelines state that patients in acute heart failure should be immediately commenced on continuous (uninterrupted) intravenous iron chelation treatment with deferoxamine 50 mg/kg/day. Deferiprone should be introduced as soon as possible at a dose of 75 mg/kg/day (the total dose given in three divided doses) 2, 20, 21, 22. At the present time, data are lacking for the use of deferasirox in acute iron overload cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Management is based on regular blood transfusions to suppress ineffective erythropoiesis, with the goal to maintain pretransfusion hemoglobin concentration above 90 g/L 2. Repeated transfusions may lead to iron overload toxicity affecting the liver, spleen, heart, and endocrine system.…”
Section: Introductionmentioning
confidence: 99%